SEPTIN10-mediated crosstalk between cytoskeletal networks controls mechanotransduction and oncogenic YAP/TAZ signaling - Weiler, Sofia Maria Elisabeth; Bissinger, Michaela; Rose, Fabian; von Bubnoff, Fabian; Lutz, Teresa; Ori, Alessandro; Schirmacher, Peter; Breuhahn, Kai (Cancer letters, 2024)
The transcriptional co-activators of the Hippo pathway, YAP and TAZ, are regulated by mechanotransduction, which depends on dynamic actin cytoskeleton remodeling. Here, we identified SEPTIN10 as a novel cytoskeletal protein, which is transcriptionally regulated by YAP/TAZ and whose overexpression correlates with poor survival and vascular invasion in hepatocellular carcinoma (HCC) patients. Functional characterization demonstrated that SEPTIN10 promotes YAP/TAZ-dependent cell viability, migration and invasion of liver cancer cells. Mechanistically, SEPTIN10 interacts with actin and microtubule filaments supporting actin stress fiber formation and intracellular tension through binding to CAPZA2 while concurrently inhibiting microtubule polymerization through the blockage of MAP4 function. This functional antagonism is important for cytoskeleton-dependent feedback activation of YAP/TAZ, as microtubule depolymerization induces actin stress fiber formation and subsequently YAP/TAZ activity. Importantly, the crosstalk between microfilaments and microtubules is mediated by SEPTIN10 as its loss abrogates actin stress fiber formation after microtubule disruption. Together, the YAP/TAZ target gene SEPTIN10 controls the dynamic interplay between actin and microtubule filaments, which feeds back on Hippo pathway activity in HCC cells and thus acts as molecular switch with impact on oncogenic signaling and cancer cell biology.